Social Capital: Trust Building As a Strategy of Developing Madrasah - Munjin Munjin (Al-Hayat Al-Istiqomah Foundation, 2017)
The developent of madrasa should not depend on financial capital, like infrastructure and media. There is another variabel which has an important role, thai is social capital. If the two variables are maximally used by the headmaster, madrasah will increase rapidly, moreover that madrasa has geneologically the big mass basis. Practically, there are many madrasas that have that two modals, but still some of them that can manage to be a power to develop madrasa. One of them is Madrasah Istiqomah Sambas Purbalingga which uses social capital, espesially trust, as a strategi in developing madrasa. How Islamic elementary school (MI) Istiqomah Sambas Purbalingga uild and manage the social capital of trust. In addition, this reseacrh will find out a good strategy in developing madrasa and strengthen the social capital. To collect data, the writer performed observation and interviewed some informans and collect some needed documentation. The collected data were then anlyzed and connected to the theory used and finally was made conclusion. The conclusion of this research is that social capital of trust was buit by philosophical, practical and institutional trust. The inclusive character of madrasa can also help to build trust.